2014
DOI: 10.1001/jamaneurol.2014.347
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Moral Judgments of Patients With Frontotemporal Dementia and Frontal Stroke

Abstract: ore than a century ago, the Phineas Gage case revealed that frontal lobe lesions can cause personality and social cognition impairment. Since its description, clinical observations 1 have highlighted important similarities between the symptoms of patients with prefrontal lesions (PFL) and patients with the behavioral variant of frontotemporal dementia (bvFTD). Both conditions share symptoms such as distractibility, personality changes, social inappropriateness, and markedly impaired moral judgments. 2,3 Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 86 publications
(80 citation statements)
references
References 19 publications
6
65
0
3
Order By: Relevance
“…This study replicated the results of a recent report [23] showing that bvFTD patients judged attempted harm as more permissible and accidental harm as less permissible than control subjects. Unlike controls, and consistently with the VBM results (see below), bvFTD patients judged attempted harm by focusing on the neutral outcome rather than the protagonist's negative intention.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…This study replicated the results of a recent report [23] showing that bvFTD patients judged attempted harm as more permissible and accidental harm as less permissible than control subjects. Unlike controls, and consistently with the VBM results (see below), bvFTD patients judged attempted harm by focusing on the neutral outcome rather than the protagonist's negative intention.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the network models, a recent study [23] demonstrated similar impairments in integrating intention and outcome information for moral judgment in patients with prefrontal lesions either with or without VMPFC damage, as well as in behavioral variant frontotemporal dementia (bvFTD) patients. Although the VMPFC may be affected in bvFTD patients, their atrophy pattern extends to other frontotemporal areas.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations